Factors associated with the morphology of the mandibular symphysis and soft tissue chin - Karine EVANGELISTA; Maria Alves Garcia Santos SILVA; David NORMANDO; José VALLADARES-NETO (Dental Press Editora, 2021)
ABSTRACT Objectives: This study aimed to (I) assess the morphology of the symphysis and soft tissue chin associated with sex, age and sagittal/vertical skeletal patterns, and (II) identify the individual and combined contributions of these variables to different portions of the symphysis. Methods: This cross-sectional study included 195 lateral cephalometric radiographs from untreated adults. Alveolar, basal, and soft tissue of the symphysis were measured by an X/Y cranial base coordinate system, and divided in accordance to four predictor variables: sex, age, and sagittal/vertical skeletal patterns. Parametric tests were conducted for comparison and correlation purposes, while multiple regression analysis was performed to explore combined interactions. Results: Alveolar inclination is related to sagittal and vertical patterns, and both explained 71.4% of the variations. Alveolar thickness is weakly predicted and poorly influenced by age. Symphysis height was 10% higher in males, and associated with a vertical skeletal pattern and sex, and both explained 43.6% of variations. Basal symphyseal shows an individual thickness, is larger in males, and vertically short-positioned with age. Soft tissue chin is not necessarily related to the size of the underling skeletal pattern, and enlarges with age, even in adulthood. Conclusions: The symphysis and surrounding tissues are influenced by sex, age, and sagittal and vertical patterns, acting differently on the alveolar, basal and soft tissue portions. Sagittal and vertical skeletal patterns are the strongest association on alveolar symphysis inclination, whereas sex and age acts on the vertical symphysis position and soft tissues thickness.